(untitled) (International journal of artificial intelligence, 2025)
The green economy provides many benefits, such as creating new jobs, developing innovative technologies, promoting sustainable business practices, and improving ecosystem services. The green economy also helps solve social and environmental problems such as poverty, climate change, and biodiversity loss. The article discusses the green economy, in addition to the granting of green entrepreneurship status in Uzbekistan.